Response of Laying Hens to Repletion and Depletion in Dietary Balanced Protein - Teodosio da Nobrega, Ingryd Palloma [UNESP]; Reis, Matheus de Paula [UNESP]; Lizana, Rony Riveros [UNESP]; Moura, Thaila Fernanda de [UNESP]; Silva Teofilo, Guilherme Ferreira da [UNESP]; Bittencourt, Leticia Cardoso; Sakomura, Nilva Kazue [UNESP] (Mdpi, 2022)
Simple Summary Considering the dynamism of the price of feed ingredients, there may be an opportunity to reduce the egg production cost by reducing the nutritional value of the feed. In this situation, it is important to understand the consequences of a feed and the ability of laying hens to recover from a previously deficient diet. This study aimed to evaluate the responses of laying hens in two scenarios of dietary balanced protein, namely, repletion and depletion. In the repletion phase, laying hens were given low dietary balanced protein (BP) in the growing phase (8 to 18 w-old), which was then changed (19 to 102 w-old) to a high dietary BP. The depletion treatment follows the opposite logic. The laying hens were monitored from 8 to 102 w-old to collect information about performance, egg quality, and body composition. The low dietary balanced protein feed affected the age at first egg and body composition, but there was a performance recovery after 19 weeks of a repletion treatment (at 38 w-old). The opposite result was observed for laying hens consuming a depleted feed. The egg components were affected only by the feed given in the laying phase. The laying hens were able to overcome a reduction in dietary balanced protein once they were given an opportunity to do so; however, in this study, 19 weeks were necessary for laying hens to achieve a steady state. This study was carried out to investigate the response of laying hens given a repletion or depletion in dietary balanced protein (BP) during the laying phase period. At the beginning of the rearing period (eight w-old), four-hundred pullets were equally distributed and received one of two experimental feeds: 1-Low BP (L) and 2-High BP (H). For the laying period (19 to 102 w-old), four feeding programs were designed based on the same treatments for rearing phases (LL, HH, LH, HL), where subsequent letters indicate the feed received during the rearing and laying period, respectively. The performance responses, egg quality, and body composition were periodically collected during the laying period. Two-way ANOVA repeated measures analysis was applied to evaluate the data. Nonlinear regression models with groups were used to compare treatments in the laying phase, with the treatments being the group evaluated. All performance traits were somehow influenced by the level of BP in the feed (p < 0.050). Hens subjected to the repletion treatment (LH) demonstrated a recovery in performance after 38 w-old. The opposite result was observed for hens on the depletion treatment (HL). All egg components were affected by dietary BP (p < 0.050). Laying hens demonstrated a limited capacity to overcome a reduction in dietary BP during production, but they were able to recover from a previous deficient feed once they were given an opportunity to do so.
Keywords: egg production; ideal amino acid profile; egg components; body composition